Pengaruh Penggunaan Pendekatan Open Ended Terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII MTs Negeri 1 Solok - Az-zahra, Fadhilah; Firmanti, Pipit; Medika, Gema Hista; Imamuddin, M (Indo-MathEdu Intellectuals Journal, 2024)
This research aims to determine the development of mathematics education in Indonesia. To overcome this problem, teachers play a role in overcoming students' learning difficulties in mathematics subjects, especially in critical thinking skills. One alternative to solve this problem is to apply open ended learning. Open ended learning is learning that presents problems by solving problems in various ways and the solutions are also varied. This research aims to find out whether the critical thinking abilities of students using an open-ended learning approach are better than the critical thinking abilities of students using conventional learning. This type of research is experimental research with circle subject matter. The population in this study was all class VIII students, totaling 91 students. The location of this research is MTs Negeri 1 Solok. The sampling technique uses random sampling. The research instrument is in the form of posttest questions. The calculation obtained ????ℎ???????????????????? > ???? 0.95;41, namely 2.84 > 2.019 and ???????????????????????? = 0.983 at the significance level α = 0.05 so it is rejected. The experimental class average was 66.71 and the control class average was 54.73.